Eksperimenti z meskalinom slovenskih psihiatrov - Valenčič, Ivan (Psihološka obzorja (Ljubljana), 1995)
After presenting a short history of peyote ingestion and the discovery of mescaline, their impact on the research by some Slovenian psychiatrists is described. More important psychiatrists who did research on mescaline from thebeginning of the 20th century to the WW II were Alfred Šerko, Mihael Kamin, Bogomir Magajna and Niko Vončina. No doubts the most important of them is Alfred Šerko, whose famous paper Im Mescalinrausch was referred to in many writings by psychiatrists, psychologists, anthropologists and even philosophers, especially after Karl Jaspers quoted it extensively in his Allgemeine Psychopatologie. Although the effect of mescaline ingestion has been known in the scientific establishment since the end of the 19th century, it was only after Šerko's article and lectures at many important European universities and institutions that mescaline attracted attention outside pharmacological academic area. Šerko's work has in a sense begotten the psychedelic movement in the western world.
Keywords: Šerko, Alfred, 1879-1938; Magajna, Bogomir, 1904-1963; Kamin, Mihael, 1898-1944; Vončina, Niko, 1905-1972; halucinogene droge; meskalin; psihoaktivne snovi; eksperimenti; zgodovina znanosti; psihiatrija; psychiatry and clinical psychology; Slovenia; Slovenija